Anatomical and functional fеatures of Deschampsia antarctica (Poaceae) leaf blade growing on the Argentine Islands - Kordyum, E.L.; Nedukha, О.M.; Ovcharenko, Y.V.; Jadko, S.I.; Ivanenko, G.F.; Loya, V.V. (Український антарктичний журнал, 2017)
The objective of the work was to perform the comparative studies of the anatomical structure and reactive oxygen species (ROS) content in leaves of Deschampsia antarctica plants growing in extreme climatic conditions of Antarctica (Skua and Galindez Іslands). Метою роботи було проведення порівняльних досліджень анатомічної структури та вмісту активних форм кисню (АФК) в листках Deschampsia antarctica (Poaceae), що росте в екстремальних кліматичних умовах Антарктики (острови Скуа і Галіндез). Целью работы было проведение сравнительных исследований анатомической структуры и содержания активных форм кислорода (АФК) в листьях растений Deschampsia antarctica (Poaceae), произрастающей в экстремальных климатических условиях Антарктики (острова Скуа и Галиндез).